2003
DOI: 10.1046/j.1365-2826.2003.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Loss Reduces Diurnal Rhythm Amplitude of Leptin in Healthy Men

Abstract: The aim of the current study was to investigate the effects of sleep loss on the diurnal rhythm of circulating leptin levels. An indwelling forearm catheter was used to sample blood at 90-min intervals for a total of 120 h, which included 88 h of sustained sleeplessness, in 10 healthy men. The diurnal amplitude of leptin was reduced during total sleep deprivation and returned toward normal during the period of recovery sleep. This finding provides evidence that sleep influences the nocturnal leptin profile, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
3
7

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(186 citation statements)
references
References 27 publications
10
161
3
7
Order By: Relevance
“…Based on both clinical and experimental studies, insufficient sleep has been shown to associate with multiple metabolic and hormonal changes including reduction in glucose tolerance, increase in cortisol levels and sympathovagal response. 11,19,22 Besides, sleep deprivation is associated with reduced leptin and increased ghrelin levels, [23][24][25] both of which can increase appetite and, hence, possibly, weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Based on both clinical and experimental studies, insufficient sleep has been shown to associate with multiple metabolic and hormonal changes including reduction in glucose tolerance, increase in cortisol levels and sympathovagal response. 11,19,22 Besides, sleep deprivation is associated with reduced leptin and increased ghrelin levels, [23][24][25] both of which can increase appetite and, hence, possibly, weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy of these results is not known, but may be due to the type I error (due to the small sample size), and the heterogeneous nature of human sample population, such as differences in living environment, nutrition, and medication status. Variation in narcolepsy symptomatology, such as degree of sleep disturbance across samples, may affect leptin results [18]. All of the factors mentioned above have been reported to affect serum leptin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-eight hours of total sleep deprivation with scheduled meals designed to maintain body weight resulted in a decrease in the amplitude of the leptin diurnal variation without change in body weight. 55 The nocturnal rise of ghrelin is modestly, but significantly, reduced during acute total sleep deprivation as compared to normal nocturnal sleep. 46 In the laboratory study that subjected healthy men to 4-hour bedtimes for 6 nights followed by 6 nights of 12-hour recovery sleep, mean leptin levels were 19% lower, the nocturnal acrophase was 2 hours earlier and 26% lower and the amplitude of the diurnal variation was 20% lower during sleep restriction.…”
Section: Laboratory Studies Of Leptin and Ghrelin During Sleep Lossmentioning
confidence: 98%